(untitled) (International Journal of Engineering and Computer Science, 2023)
This paper delves into the multifaceted security implications of blockchain technology. Blockchain’s decentralized and immutable nature has transformed various industries, but it also presents unique challenges and risks. The study investigates the vulnerabilities, threats, and potential mitigations in blockchain-based systems, offering insights into the evolving landscape of cybersecurity in the context of distributed ledger technology. The analysis encompasses topics such as consensus algorithms, smart contracts, cryptographic mechanisms, and privacy concerns, shedding light on the critical need for robust security measures to harness the full potential of blockchain technology while safeguarding against emerging threats. This paper also explores the security implications of blockchain technology, with a focus on its impact and relevance in contemporary digital landscapes. As blockchain gains widespread adoption across various industries, understanding its security aspects becomes paramount. The study delves into the core security features of blockchain, such as decentralization, cryptographic hashing, and consensus mechanisms, while also discussing potential vulnerabilities and threats. Additionally, it investigates real-world use cases and examples of security breaches in blockchain systems. The findings highlight the importance of robust security measures and best practices for harnessing the full potential of blockchain technology, making it a valuable resource for researchers seeking insights into this dynamic and complex field.